2005
DOI: 10.1051/vetres:2004055
|View full text |Cite
|
Sign up to set email alerts
|

High milk neutrophil chemiluminescence limits the severity of bovine coliform mastitis

Abstract: -Polymorphonuclear neutrophil (PMN) function changes during mastitis. To investigate the contribution of milk PMN to the severity of Escherichia coli (E. coli) mastitis, chemiluminescence (CL) of blood and milk PMN and their efficiency to destroy coliform bacteria in the mammary gland were examined following the induction of E. coli mastitis in early lactating cows. To better assess and define the degree of mastitis severity, cows were classified as moderate and severe responders according to milk production l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
99
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(110 citation statements)
references
References 43 publications
8
99
0
3
Order By: Relevance
“…In vivo studies have demonstrated that the life span of bovine PMN from mammary quarters infected with E. coli is prolonged when compared to noninfected quarters [25]. Further, higher preinfection viability of mammary PMN correlated with increased chemiluminescence activity, a more rapid bacterial clearance and recovery of infected quarters [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have demonstrated that the life span of bovine PMN from mammary quarters infected with E. coli is prolonged when compared to noninfected quarters [25]. Further, higher preinfection viability of mammary PMN correlated with increased chemiluminescence activity, a more rapid bacterial clearance and recovery of infected quarters [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…According to MEHRZAD et al (2005) and MERLE et al (2007), SCCs do not seem to describe completely the defense activities within the udder, which require the determination of functional parameters such as viability and activity of PMNs.…”
Section: Resultsmentioning
confidence: 99%
“…These are the most abundant and the most important phagocytes of the innate immunity and they constitute more than 90% of somatic cells in cows with clinical mastitis (Sharma et al, 2011). If neutrophils are effective as antimicrobial defences, they are also a putative source of molecules with proinflammatory and proteolytic roles which harm the mammary epithelium (Capuco et al, 1986;Mehrzad et al, 2005). In such cases, a therapeutic approach is to treat cows with anti-inflammatory agents (McDougall et al, 2009).…”
Section: Discussionmentioning
confidence: 99%